Automated Reasoning: 12th International Joint Conference, IJCAR 2024, Nancy, France, July 3–6, 2024, Proceedings, Part I - Benzmüller, Christoph; Heule, Marijn J. H; Schmidt, Renate A (Lecture Notes in Computer Science; Lecture Notes in Artificial Intelligence, 2024)
This two-volume set of LNAI 14739-14740 constitute the proceedings of the 12th International Joint Conference on Automated Reasoning, IJCAR 2024, held in Nancy, France, during July 3-6, 2024. The 39 full research papers and 6 short papers presented in this book were carefully reviewed and selected from 115 submissions. The papers focus on the following topics: theorem proving and tools; SAT, SMT and Quantifier Elimination; Intuitionistic Logics and Modal Logics; Calculi, Proof Theory and Decision Procedures; and Unification, Rewriting and Computational Models. This book is open access.